Using Purchasing Managers’ Index (PMI) Methodology to Develop a New Customer Satisfaction Measure. - Grzegorz BIESOK; Jolanta WYRÓD-WRÓBEL (Communications of International Proceedings, 2022)
The purpose of this paper is to propose a new customer satisfaction measures: customer satisfaction index and customer repurchasing intentions index modelled on the Purchasing Managers' Index (PMI) and to verify their functioning using the results of several customer satisfaction surveys conducted in various industries. Based on PMI methodology, we proposed formulas to calculate customer satisfaction index (SI) and customer repurchasing intentions indices (RI). Then we compared proposed indices with other satisfaction measures. In the result we found out that the proposed SI is highly correlated with other measures of satisfaction.
Keywords: customer satisfaction; customer satisfaction measurement; index methods; Purchasing Managers’ Index